The spectacled porpoise (Phocoena dioptrica) in Antarctic waters - Sekiguchi , Keiko; Olavvaria , Carlos; Morse, Laura; Olson , Paula; Ensor , Paul; Matsuoka , Koji; Pitman , Robert; Findlay , Ken; Gorter , Uko (J. Cetacean Res. Manage., 2023)
Most knowledge on the biology and ecology of the spectacled porpoise (Phocoena dioptrica) has been obtained from stranded specimens, with less than fifteen confirmed sightings in the sea. Published photographs of live animals in their natural environment are also very rare. In this study, 28 live sightings are summarised, from Antarctic and sub Antarctic waters (mainly from the 1978-2004 IWC-IDCR/SOWER cruises). These sightings supported the suggested circumpolar and offshore distribution of this species; however, this was extended further south than previously thought, into Antarctic waters. The sea surface temperature recorded at the time of each sighting ranged from 0.9- 10.3°C, with most of the sightings (52.0%) in waters 4.9-6.2°C. Group size was small, averaging 2.0 (SD=0.92) animals per group. A total of six cow-calf pairs were observed and all such pairs were accompanied by one or two additional adults, always including a mature male. Based on observations at sea and new photographs of live animals, a pale ‘saddle’ around the dorsal fin was noticed and is described for the first time. The porpoises generally showed fast swimming behaviour when the vessel approached, resembling the swimming behaviour of harbour porpoises.